Challenges and Prospects for Providing Radiation Oncology Services in Africa - Balogun, Onyinye (Semin Radiat Oncol, 2016)
There are considerable challenges to meeting the demands of the impending cancer crisis in Africa. These include a rising incidence of cancer and cancer-related deaths, equipment and maintenance costs, and deficits in human resources and training. Addressing these issues would be crucial to tackling the increasing burden of cancer on the continent. Innovations in technology and collaborative efforts within the global oncology community have created promising solutions for establishing quality cancer care in Africa and eradicating the massive disparities that currently exist. A multifaceted approach that establishes access to quality radiation oncology services is needed to curtail this alarming trend. In this article, we describe the current status of radiotherapy services in Africa, barriers and opportunities to improve this integral component of comprehensive cancer care.